Assessing the stress-relief impact of an art-based intervention inspired by the broaden-and-build theory in college students - Liu, Chen; Xie, Yuan; Xu, Yiwen; Song, Zhenhai; Tang, Jiayi; Shen, Junjie; Jiang, Zhou; Shen, Chao; Zhan, Xingya; Zheng, Chu (Frontiers in Psychology, 2024)
Background and objectives This study’s primary objective is to investigate the impact of art-making on the mental well-being of college students, who often experience heightened stress during their initial university years. Methods Employing a comprehensive methodology, combining interviews and the Perceived Stress Scale (PSS), the research aimed to assess whether a four-week art-making intervention can effectively alleviate stress levels among college students. In the experimental group, participants engaged in a variety of art-making activities, including freehand drawing, clay modeling, and crafting. Results The results revealed that, in the pre-test, there were no significant differences between the experimental and control groups for each assessed indicator. However, in the post-test, significant differences emerged across all indicators. Further analysis demonstrated a significant reduction in stress perception among the experimental group participants between the pre-test and post-test phases. Conclusion In conclusion, this study provides compelling evidence that art-making has the potential to foster positive personal development and significantly reduce stress levels among college students.